2006
DOI: 10.1051/rnd:2005065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod length on body mass and testicular growth in the house sparrow (Passer domesticus) and brahminy myna (Sturnus pagodarum)

Abstract: -Two experiments studied the relative effects on body mass and testicular growth of stimulatory photoperiods applied simultaneously to two photosensitive species, the house sparrow (Passer domesticus) and brahminy myna (Sturnus pagodarum).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…In the animals of the present study, a positive correlation was observed between the degree of spermatogenic development and the diameter of the seminiferous tubules (Table ). Thus, in accordance with all the findings that indicated a higher reproductive activity in A. leucophthalma and in other species of birds studied (Wikelski et al., ; Kim and Yang, ; Madekurozwa et al., ; Bhardwaj and Anushi, ), the diameter of the seminiferous tubules and the degree of spermatogenic development were significantly higher in the spring than in the fall (Table ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the animals of the present study, a positive correlation was observed between the degree of spermatogenic development and the diameter of the seminiferous tubules (Table ). Thus, in accordance with all the findings that indicated a higher reproductive activity in A. leucophthalma and in other species of birds studied (Wikelski et al., ; Kim and Yang, ; Madekurozwa et al., ; Bhardwaj and Anushi, ), the diameter of the seminiferous tubules and the degree of spermatogenic development were significantly higher in the spring than in the fall (Table ).…”
Section: Discussionsupporting
confidence: 90%
“…The seasonal reproductive activity observed in male birds describes a cyclical activity involving phases of quiescence during the period of reproduction rest and of spermatogenic recrudescence during the mating periods (Lofts and Murton, ). Then, similarly to what happens to other seasonal birds throughout the year, different degrees of spermatogenic development were observed in A. leucophthalma , directly related to the testicular size, volumetric proportion and the diameter of the seminiferous tubules (Wikelski et al., ; Kim and Yang, ; Madekurozwa et al., ; Bhardwaj and Anushi, ). In the animals of the present study, a positive correlation was observed between the degree of spermatogenic development and the diameter of the seminiferous tubules (Table ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These measures also tended to change in tandem with changes in age and body weight. A similar relationship was reported by Bhardwaj and Anushi (2006) in house sparrows ( Passer domesticus ) and by Deviche et al . (2001) in dark-eyed junco ( Junco hyernalis) under the altered photoperiod regimens.…”
Section: Discussionsupporting
confidence: 90%
“…these data tend to increase in increased body weight and age. A similar pattern of relationship was reported in sparrows (Passer domesticus) [19] . A positive relationship among various physiological traits was also published in male Japanese quail [15] .…”
Section: Discussionsupporting
confidence: 82%